A Neuro-Fuzzy Controller for Collaborative Applications in Robotics Using LabVIEW. (14th July 2009) - Ponce, Hiram E.; Araiza, Dejanira; Ponce, Pedro
Abstract : A neuro-fuzzy controller was designed and implemented using LabVIEW over a mobile robotic platform. The controller is based on fuzzy clusters, neural networks, and search techniques. Also, wireless communication with Bluetooth protocol was used to communicate the robot with the controller running in LabVIEW, allowing a simple collaborative task that consisted in pick and place objects, through knowing the position of the robot and measuring the distance to the objects. The neuro-fuzzy controller was split in two parts: the position controller and the evasion controller against collisions.